Critical Evaluation of an ELT Coursebook in a Globalisation Context - Erpin Said; Muhaiminah Akib; Hayat Marwan Ohorella (Qalam : Jurnal Ilmu Kependidikan, 2021)
The purpose of this study is to discuss what has made an English Coursebook and outline the positive and negative consequences of globalisation on English Language Teaching (ELT). This study adopts the framework of globalisation context proposed by Block and Cameron. The data in this study cover all the coursebook content that show positives and negatives consequences, with total 13 examples in 116 pages. The findings show that there are several beneficial impacts of using this coursebook as it succeeds in covering the local culture. This study shows 10 examples that cover positive consequences in this coursebook. However, this coursebook also has several negative consequences. It lacks integration with international culture, of which it contains only two examples. However, the positive outweighs the drawbacks.